Root Characteristics of Different Rice Varieties under Two Different Hydrological Situations as Influenced by Methods of Establishment in Wet Season - Das, Priyanka; Gulati, J. M. L.; Pattanayak, Sarthak (International Journal of Bio-resource and Stress Management, 2016)
Field experiment was conducted on Agronomy Main Research Farm, Department of Agronomy, Orissa University of Agriculture and Technology on kharif 2015 taking six crop establishment methods and three varieties under aerobic (Non puddled-Non flooded) condition while 5 establishment methods and three varieties under anaerobic (Puddled-flooded) condition in observation strip to study on root traits of different rice varieties under two hydrological situations of aerobic and anaerobic condition revealed that, all the root traits recorded higher values with aerobic transplanting (20×20 cm2) and modified SRI (20×20 cm2) under aerobic and anaerobic conditions, respectively. Aerobic (25×25 cm2) and conventional transplanting recorded higher root-length ratio of 3.82 and 2.55 under aerobic and anaerobic situations respectively. The ratio of root length to root dry weight was however, higher with direct seeding (29.83) and conventional planting (22.2) under similar situations aerobic rice. On an average, across the methods, aerobic condition registered an increase of 13.2% in mean root length over anaerobic one (27.2 cm) whereas, the extent of increase in mean root spread and root dry weight was 3 and 5.9% under an aerobic condition over aerobic condition with corresponding absolute values of 26.7 cm and 121 g. Pyari measured longest roots (43.34 cm) under aerobic and highest root dry weight (2.73 g hill-1) under anaerobic condition while Naveen recorded maximum horizontal spread (19.3 cm) under an aerobic and root volume (28.0 cc) under aerobic conditions. Root length-spread ratio (6.28) and root length-root dry weight ratio (25.60) was highest with Naveen under aerobic situation.